PERAN SATUAN LALU LINTAS KEPOLISIAN RESOR KOTA PEKANBARU DALAM MENANGANI MASALAH PELANGGARAN RAMBU LALU LINTAS DILARANG PARKIR DI KECAMATAN PEKANBARU KOTA - Tomi Jefisa; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Each person uses a motor vehicle to facilitate its activities to mobilize or move from one place to another in everyday life, be it a two-wheeled vehicle or four wheels. Motor vehicle is any vehicle that is driven by mechanical equipment such as engines other than vehicles running on rails. As motorists must give priority to the safety and comply with the applicable regulations in accordance with the provisions in force in the State Indonesia. Pursuant to Article 106 paragraph (4) (a) and letter (e) of Law Number 22 Year 2009 regarding Traffic and Road Transportation. The research objective of this thesis, namely; First, to determine the role of Pekanbaru City Traffic Police, Second, To know the constraints faced by the City Police Traffic Pekanbaru, Third, To know the efforts made by the City Police Traffic Pekanbaru.Keywords: Role - Traffic Unit - No parking signs